2017
DOI: 10.3928/00220124-20170321-08
|View full text |Cite
|
Sign up to set email alerts
|

Increasing RN Perceived Competency With Substance Use Disorder Patients

Abstract: Nurses working in acute care hospitals, particularly those without addiction and psychiatric services, may benefit from continuing education on this important topic. J Contin Nurs Educ. 2017;48(4):175-183.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…Only two studies used the same instrument (Corrigan et al, 2018;Rosenthal et al, 2018) therefore comparing outcomes between interventions was limited. Opioid use disorder educational needs of medical-surgical nurses were identified by institutional survey results (Naqib et al, 2018), self-reported knowledge gaps (Rosenthal et al, 2018;Tran et al, 2009b), and an institution identified need secondary to an increased population of patients with OUD in medical-surgical areas (Corrigan et al, 2018;Graham, Christy, Emmitt-Myers, & Zyzanski, 1997;Puskar et al, 2016;Russell et al, 2017;Sargsyan, Metcalfe, Turner, & Fouts, 2013;Tran et al, 2009b). Once identified, educational programmes were developed to increase competency in the areas of need.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two studies used the same instrument (Corrigan et al, 2018;Rosenthal et al, 2018) therefore comparing outcomes between interventions was limited. Opioid use disorder educational needs of medical-surgical nurses were identified by institutional survey results (Naqib et al, 2018), self-reported knowledge gaps (Rosenthal et al, 2018;Tran et al, 2009b), and an institution identified need secondary to an increased population of patients with OUD in medical-surgical areas (Corrigan et al, 2018;Graham, Christy, Emmitt-Myers, & Zyzanski, 1997;Puskar et al, 2016;Russell et al, 2017;Sargsyan, Metcalfe, Turner, & Fouts, 2013;Tran et al, 2009b). Once identified, educational programmes were developed to increase competency in the areas of need.…”
Section: Discussionmentioning
confidence: 99%
“…Educational activities included interactive workshops and case studies (Naqib et al, 2018), online modules (Puskar et al, 2016;Rosenthal et al, 2018), live classroom sessions (Graham et al, 1997;Naqib et al, 2018;Rosenthal et al, 2018;Russell et al, 2017;Tran et al, 2009aTran et al, , 2009b, simulation sessions and real-time coaching (Puskar et al, 2016;Rosenthal et al, 2018) scenario versus scenario with simulation and debriefing (Corrigan et al, 2018) and an online continuing education offering (Sargsyan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations